Association of Metabolite Concentrations and Water Diffusivity in Normal Appearing Brain Tissue with Glioma Grade. Issue 6 (19th November 2013) - Maudsley, Andrew A.; Roy, Bhaswati; Gupta, Rakesh K.; Sheriff, Sulaiman; Awasthi, Rishi; Gu, Meng; Husain, Nuzhat; Mohakud, Sudipa; Behari, Sanjay; Spielman, Daniel M.
ABSTRACT: BACKGROUND AND PURPOSE: Studies of brain tumors have identified altered tissue metabolism and water diffusion in MRI normal appearing tissue regions. In this retrospective study the relationship of these imaging measures with tumor grade in gliomas was investigated. METHODS: MR spectroscopic imaging of whole brain and mean diffusivity (MD) measurements were obtained in subjects with untreated glioma and from normal control subjects. Mean metabolite values for N‐acetylaspartate (NAA), total creatine (Cre), and total choline (Cho) were obtained in gray‐ and white‐matter regions for the hemisphere contralateral to the tumor location, and MD values were obtained from contralateral normal‐appearing white matter. Analyses tested for differences in mean values between subject groups while accounting for age. RESULTS: Analysis demonstrated increased NAA/Cre and MD, and decreased Cho/NAA for all tumor grades relative to control values. Differences between tumor grades were also observed for NAA, NAA/Cre, and Cho/NAA. Abnormal values of water diffusion were also observed, but with only a weak association between alterations in diffusion and tissue metabolites. CONCLUSIONS: This study supports previous observations of altered tissue metabolism and water diffusion in normal‐appearing white matter while additionally finding differences of metabolite values in gray matter and an association with tumor grade.